PECULIARITIES OF TRAINING FUTURE SBGS OFFICERS FOR SHIP ADMINISTRATION IN MARITIME GUARD DETACHMENTS - Sahan, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2021)
One of the main functions of the State Border Guard Service of Ukraine is the protection of the state border of Ukraine on land, sea, rivers, lakes and other bodies of water; protection of the sovereign rights of Ukraine in its exclusive (maritime) economic zone and control over the implementation of rights and fulfilment of obligations by other countries in this zone. The structure of the Border Guard Service of Ukraine includes the Maritime Guard, which consists of Maritime Guard Detachments. The State Border Guard Service of Ukraine organizes training and retraining of its servicemen in educational institutions. The Bohdan Khmelnytskyi National Academy of the State Border Guard Service of Ukraine is such an institution in the border protection system. The article analyses the peculiarities of training future officers of the State Border Guard Service of Ukraine to conduct ship administration in the Maritime Guard Detachments of the State Border Guard Service of Ukraine. The scientific attention was drawn by having identified certain problematic issues that arose in the training process organization of specialists for service in the Maritime Guard Regional Department of the Border Guard Agency – three Maritime Guard Detachments and the Maritime Guard Training Centre. Ship administration in the Maritime Guard Detachments provides support for operational and service activities, combat (professional) training, work with personnel, household, proper operation, repair, storage of weapons, military equipment and property. At the same time, as a result of scientific analysis of educational and professional programs (working programs of disciplines, practical training programs) of the National Academy, it has been established that there are no topics about the main provisions for the organization of ship administration in bodies, institutions and establishments of the State Border Guard Service of Ukraine. The article also proposes to develop ways to resolve the contradiction between the emergence of the logistics section on headquarters of a rapid response border command and the lack of planning changes in the educational process of the National Academy of the State Border Guard Service of Ukraine. The author highlights the results of the above analysis, including the facts of low qualification of officers in the field of ship administration, and focuses on the importance of taking into account in the issues of conducting ship administration in the educational process of the SBGS educational institutions, based on the requirements of departmental guidelines for proper professional training of relevant officials.
Keywords: military administration, ship administration, maritime guard, maritime guard detachment, State Border Guard Service of Ukraine